From the definition of a logarithm:

When you get

Hence and since then

==========================

Alternatively think of them as inverse operations which "cancel"

Results 1 to 2 of 2

- Mar 26th 2011, 09:45 AM #1

- Joined
- Feb 2010
- Posts
- 50

## exp(log(3))=3 or e^ln(3)=3, why?

exp(log(3))=3 or e^ln(3)=3, why?

I am reading an explanation like this:

"3 is the end result of growing instantly (using e) at a rate of ln(3). 3 = e^ln(3)"

BUT I cannot understand it... actually I don't understand so well, e as well ln ... please try to explain me while keeping this things in the mind - THANKS

- Mar 26th 2011, 09:59 AM #2